Performance of Ti-6242 production using nano powder mixed with different dielectrics - Shather, Saad Kariem; Sapit, Azwan; Abed, Farook Nehad (Elsevier, 2021)
The recent scenario of modern manufacturing is tremendously improved in the sense of precision machining and abstaining from environmental pollution and hazard issues. In the present work, Ti6242 is machined through wire EDM (WEDM) process with powder mixed dielectric and analyzed the influence of input parameters and inherent hazard issues. WEDM has different parameters such as peak current, pulse on time, pulse off time, gap voltage, wire-speed, wire tension, and so on, as well as dielectrics with powder mixed. These are playing an essential role in WEDM performances to improve the process efficiency by developing the metal removal rate. Even though the parameter’s influencing, the study of the nano dielectric effect in the WEDM process is very essential during the machining process due to the high discharge energy. In the present study, two different dielectric fluids were used, including deionised water, and nanopowder dielectrically, and analyzed the data by taking the response surface method to use program design expert 10. From this study, it is established that dielectric types and powder significantly improve performances with a proper set of machining parameters and find out the risk factor associated with the WEDM process.